درجة توافر المعايير الرياضية للدراسة الدولية TIMSS لدى معلمات الرياضيات بمكة المكرمة من وجهة نظر المعلمات والمشرفات - كوسة، سوسن عبدالحميد محمد; الزبيدي، معينة بنت سند أحمد (جامعة المنصورة - كلية التربية, 2019)
درجة توافر المعايير الرياضية للدراسة الدولية ((TIMSS لدى معلمات الرياضيات بمكة المكرمة من وجهة نظر المعلمات والمشرفات. هدفت الدراسة إلى التعرف على درجة توافر معايير الدراسة الدولية (TIMSS 2015) لدى معلمات الرياضيات بمكة المكرمة من وجهة نظر معلمات ومشرفات الرياضيات، ولتحقيق الهدف تم إعداد استبانة والتأكد من صدقها وثباتها، ومن ثم طبقت على عينة من معلمات ومشرفات الرياضيات عددهن (١٣٩). وبعد جمع البيانات ومعالجتها إحصائياً، تم التوصل إلى النتائج التالية: ١-درجة توافر معايير الدراسة الدولية (TIMSS 2015) لدى معلمات الرياضيات بمكة المكرمة من وجهة نظر المعلمات والمشرفات درجة كبيرة حيث بلغ المتوسط الوزني للدرجات الكلية للمعايير 4.013 بانحراف معياري 0.900. ٢-أظهرت وجود فروق دالة إحصائيا عند مستوى 0.01 في استجابات أفراد عينة الدراسة حول درجة توافر معايير الدراسة الدولية (TIMSS 2015) لدى معلمات الرياضيات بمكة المكرمة تبعا لمتغير الوظيفة لصالح المعلمات، ولمتغير المرحلة الدراسية لصالح المرحلة الابتدائية. ٣-أظهرت نتائج الدراسة عدم وجود فروق دالة إحصائياً في استجابات أفراد عينة الدراسة حول درجة توفر معايير الدراسة الدولية (TIMSS 2015) لدى معلمات الرياضيات بمكة المكرمة فيما يتعلق بمعايير (المهارات المعرفية الرياضية، المعيار الشخصي) تبعاً لمتغير سنوات الخبرة. بينما أظهرت وجود فروق فيما يتعلق بمعايير (النمو المهني للمعلمات، القدرة على بناء عادات العقل المنتجة، بناء علاقات مع الزميلات، مواكبة التطورات التربوية الحديثة في مجال التعليم، مهارات المعلومات والتقنية) ترجع لاختلاف سنوات الخبرة لصالح خبرة أقل من ٥ سنوات. 4-عدم وجود فروق دالة إحصائيا في استجابات أفراد عينة الدراسة حول درجة توفر معايير الدراسة الدولية (TIMSS 2015) لدى معلمات الرياضيات بمكة المكرمة ترجع لاختلاف عدد الدورات التدريبية. وأوصت الباحثتان عدد من التوصيات أهمها تطوير برامج تدريبية لمعلمات الرياضيات تحقق النمو المهني لهن تبعا للمستجدات العلمية الخاصة باستراتيجيات تدريس الرياضيات، والمتابعة والتقييم من قبل وزارة التعليم لمعلمات الرياضيات اللاتي يتم تدريبهن على معايير الدراسة الدولية (TIMSS 2015)، وإثراء منهج الرياضيات بمعلومات وأنشطة تشمل كافه معايير الدراسة الدولية TIMSS 2015)).
The study aimed at identifying the degree of availability of the Mathematics' standards of international study (TIMSS) among the mathematics teachers in Makkah from the point of view of the teachers and supervisors of mathematics in Makkah, To achieve the goal, a questionnaire was prepared to verify its validity and reliability, and then applied to a sample of the mathematics teachers and supervisors (139). After collecting and processing the data statistically, the following results were obtained: 1- The availability of the Mathematics' standards of the international study (TIMSS) among the mathematics teachers in Makkah from the point of view of the teachers and supervisors is very high, where the average mean of the total scores of the standards was 4.013 with a standard deviation of 0.900. 2-There were statistically significant differences at the level of 0.01 in the responses of the members of the study sample on the degree of availability of the Mathematics' standards of international study (TIMSS) among the mathematics teachers in Makkah according to the job variable in favor of the teachers and the variable of the stage for the primary school. 3-The results of the study showed no statistically significant differences in the responses of the sample of the study on the degree of availability of the standards of the international study (TIMSS) among the mathematics teachers in Makkah in terms of the standards of (mathematical cognitive skills, personal criterion) according to the variable years of experience whereas it showed differences in regards of the standards of professional growth of teachers, ability to form productive habits of the mind, form relationships with colleagues, keeping pace with modern educational developments in information and technical skills due to different years of experience in favor of less than 5 years experience. 4- There are no statistically significant differences in the responses of the study sample members on the degree of availability of the Mathematics' standards of international study (TIMSS) among the mathematics teachers in Makkah due to the different number of training courses. The researchers recommended a number of recommendations, the most important of which is the development of training programs for mathematics teachers to achieve their professional growth according to the scientific developments in mathematics teaching strategies, follow-up and evaluation by the Ministry of Education for mathematics teachers who are trained in the standards of international study (TIMSS), and enrich the mathematics curriculum with information and activities, covering all the International Study Standards (TIMSS).
Keywords: العملية التعليمية -- الأساليب التدريسية -- المواد الدراسية -- تعلم الرياضيات -- مكة المكرمة